Left main revascularization with optical coherence tomography in a young male with newly diagnosed homozygous familial hypercholesterolemia. Issue 1 (January 2022) - Revaiah, Pruthvi C.; Bootla, Dinakar; Vemuri, Krishna Santosh; Nevali, Krishna Prasad; Ghosh, Soumitra; Sharma, Yash Paul; Panda, Prashant
Abstract: Familial hypercholesterolemia is the most common primary lipid disorder responsible for coronary artery disease. A 22-year-old male presented with history of accelerating angina and extensive xanthomatous lesions all over the body. Coronary angiography showed significant left main and left anterior descending artery disease. Optical coherence tomography (OCT) imaging revealed areas of lipid rich plaque with thin capped fibrous atheroma, and inflammatory cell infiltration. Area of maximum stenosis showed fibrous plaque with dense lipid pool. OCT in this patient clarified plaque characteristics and achieved optimal procedural results. There were only few case reports which described OCT findings in patients with familial hypercholesterolemia. <Learning objective: Undiagnosed familial hypercholesterolemia may present with life-threatening complications. The index case presented with critical left main disease. Intravascular imaging is necessary in patients with primary lipid disorders undergoing percutaneous coronary intervention, which characterizes plaque, the index case had densely lipid rich plaque with areas of inflammation. Characterizing plaque characteristics in patients with lipid disorders might have an impact on the management of these patients, which needs to be clarified in appropriately sized studies.>